Al- Qaida in the Maghreb: Just a new name or indeed a new threat? - Guido Steinberg; Isabelle Werenfels (Stiftung Wissenschaft und Politik (SWP), 2007)
The strongest armed faction in Algeria has changed its name to 'al-Qaida in the Islamic Maghreb', thus announcing a move towards internationalisation. It is not clear whether the group, in its weakened state, has simply adopted a new handle for recruitment purposes or whether it aims to step up its activities outside Algeria. The second alternative seems likely as the group is attempting to extend its operational area to the neighbouring states and to extend its recruiting activities in Morocco and Tunisia. Regardless of the actual magnitude of the terrorist threat, these efforts are likely to trigger a sequence of negative consequences, in that increased activities by the group will prompt the Maghreb states to increase their repressive measures and intensify their military cooperation with the USA. Both these responses have been shown to encourage armed groups in the past. Thus Europe would be wise to insist on the observance of human rights and due legal procedures despite the necessity of cooperation in security matters.(SWP Comments / SWP)
Keywords: 320